Observations from a series of flume experiments on contraction scour along a rectangular channel - Nowroozpour, Alireza, author; Ettema, Robert, advisor; Julien, Pierre, committee member; Nelson, Peter, committee member; Zevenbergen, Lyle, committee member; Gallen, Sean, committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.
Keywords: contraction; open channel flow; sediment transport; contraction hydraulic; bridge design; scour